2015
DOI: 10.1007/s12193-015-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cognitive gamification: general framework for educational games

Abstract: Gamification of learning material has received much interest from researchers in the past years. This paper aims to further improve such learning experience by applying socio-cognitive gamification to educational games. Dynamic difficulty adjustment (DDA) is a well-known tool in optimizing gaming experience. It is a process to control the parameters in a video game automatically based on user experience in real-time. This method can be extended by using a biofeedback-approach, where certain aspects of the play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There is plenty of models and frameworks guiding gamification design and development in different domains (Choi & Choi, 2021;B. Huang & Hew, 2018; J. T. Kim & Lee, 2015;Morschheuser et al, 2017;Szegletes, Koles, & Forstner, 2015;Wells et al, 2014;Wongso, Rosmansyah, & Bandung, 2014) and with different goals. However, most of them are not detailed enough to provide sufficient practical guidance, and some of them lack a detailed description of the design phase (Morschheuser et al, 2017).…”
Section: Holistic Modelmentioning
confidence: 99%
“…There is plenty of models and frameworks guiding gamification design and development in different domains (Choi & Choi, 2021;B. Huang & Hew, 2018; J. T. Kim & Lee, 2015;Morschheuser et al, 2017;Szegletes, Koles, & Forstner, 2015;Wells et al, 2014;Wongso, Rosmansyah, & Bandung, 2014) and with different goals. However, most of them are not detailed enough to provide sufficient practical guidance, and some of them lack a detailed description of the design phase (Morschheuser et al, 2017).…”
Section: Holistic Modelmentioning
confidence: 99%
“…Based on the analysis of related practices, it can be found that there is a clear trend when exploring BCI games in different application areas. The Octalysis framework combines the advantages of BCIs of enriching the interaction forms and realizing game control directly by brain signals [ 51 ] with the advantage of gamification that provides attractiveness, which can greatly improve the task accomplishment channels and training adherence. Moreover, the multimodal interaction brought by a BCI game can greatly enhance a user’s enthusiasm, improve a user’s acceptance, assist in the effective execution of related tasks and lead to the precise detection and estimation of the user’s state [ 52 ].…”
Section: Related Workmentioning
confidence: 99%
“…A major benefit of using Unity is that it opens the potential for future deployment of our app to additional platforms such as iOS, PC/laptop, virtual reality or augmented reality headsets, games consoles and smartTVs. Such deployment to these platforms in conjunction with the io:bio EEG system could be used to advance neurofeedback systems [29,78,86], gamification projects [87][88][89] and BCI testbeds [90,91]. There is opportunity for future expansion of the features on our smartphone app by utilising Unity.…”
Section: A Development Of the Smartphone-based Eeg Systemmentioning
confidence: 99%